Leonid A. Kurdachenko (dedicated to 70th Birthday) (Algebra and Discrete Mathematics, 2020)
Leonid A. Kurdachenko is definitely one of the most productive group theorists. His list of publications consists of more than 250 journal articles published in major mathematics journals in many countries including Ukraine, USA, Germany, Great Britain, Italy, Spain, China, Greece, Brazil, Hungary, Poland, Czech Republic, Turkey, and Russia. He is an author of more than a dozen of books published by such prestigious publishers as John Wiley & Sons (USA), Birkhäuser (Swiss), World Scientific (United Kingdom), and others. He is a very popular invited speaker and visiting professor in many international conferences and universities, including University of Zaragoza, University of Naples, University of Salerno, University of Alabama, and others. He supervised 9 Ph.D. students and a D.Sc. student who actively work in algebra. His input in the development of Ukrainian algebra is difficult to overestimate.